Social Security in a "Moral Economy": An Empirical Analysis for Java - Ravallion, Martin; Dearden, Lorraine (The Review of Economics and Statistics, 1988)
Private transfer payments are modeled as outcomes of a constrained social choice pro blem facing donors. The approach is applied to a large household leve l data set for Java and hypotheses are tested concerning the performa nce of the "moral economy" as a social security system. Transfer be havior is found to be very different between rural and urban areas. W hile transfer receipts and outlays are income inequality reducing in rural areas, this is not the case in urban areas. There is also evidence of transfers being targeted to disadvantaged households such as the sick, elderly, and (for urban areas) the unemployed. Copyright 1988 by MIT Press.